Historical Analysis of Ethnic Conflict in Nigeria, 1990-2013 - Olayinka Olabimpe Ojo; Bello, T.T (Britain International for Academic Research (BIAR-Publisher), 2022)
Conflict is as old as human race. Since the creation of the country called Nigeria, there has been debate on the issue of peaceful coexistence among the different ethnic groups and between the two major religious groups, Christians and Muslims. This paper explored ethnic conflicts in Nigeria. There are many research work has been carried upon on the issue of Ethnic conflicts in Nigeria but the implications of these on the girl-child is limited. It is on this premise that this research is based. Ethnic issues are the bane of the different conflicts in Nigeria. It is against this background that this study intends to undertake a critical investigation of the ethnic conflict. The significance of this study therefore cannot be overemphasized because there cannot be development if there is no peace. However, the entrenchment of the democratic rule in 1999 brought a ray of hope for the citizens. Sadly, democracy has failed to completely unite the people of Nigeria; this is evident in the scores of ethnic conflicts in different parts of the nation.